Ash formation and trace elements associations with fine particles in an ultra-low emission coal-fired power plant. (15th March 2021) - Tian, Chong; Gong, Bengen; Wang, Xiaochuan; Zhao, Yongchun; Zhang, Junying
Highlights: Alternations of surface chemistry of PM would eventually affect TEs migrations. PM escaped from WESP are abundant in Ca and S, thus causing retention and accumulations of As, Cu, Zn, and Pb. Particle size would affect TEs distributions in PM. As and Pb enrich in PM of 0.5µm, and Cu and Zn enrich in PM of 1µm. Associations of As, Cu, and Pb with other species in single particles are presented. Abstract: To meet the strict environmental requirements, air pollutions control devices are commonly installed in coal-fired power plants in China. Better understanding of porperties of particulate matters and trace elemetns associations are important for comprehensive evaluations on environmental impacts caused by the ultra-low emiission retrofits. This work have analyzed ash formaion and trace elements emissions as well as their associations with particulate matters in an ultra-low emission coal-fired power plant. The results indicate that ultra-low emission retrofits would greatly reduce particulate matters emissions, and trace elements distributions in bottom ash, fly ash, and fine particles are not significant changed. However, it would affect trace elements distributions in particulate matter from different sampling sites, which is due to the alternations on ash fromation caused by the change of local reaction conditions, thus affecting the particualte matter properties and trace elements migration behaviors. Electrostatic precipitator and wet electrostatic precipitator are capable for most of trace elements laden particle matter removal, but the particulate matters escaped from wet electrostatic precipitator are enriched in As, Cu, Zn, and Pb. Particle size would affect those 4 kinds of trace elements distributions in fly ashes. As and Pb would accumulate in particles with size decreasing in the fractions from 10 μm to 0.5 μm. While Cu and Zn enrich in particles in size fractions of 1 μm. The associations of As, Cu, and Pb with other species in a single particle are also presented, which would be helpful for understanding the trace elements migration and accumulation behaviors in particulate matter.